Model Evaluasi Pembelajaran Berbasis Media Visual untuk Penguatan Nilai Pendidikan Agama dan Budi Pekerti pada Siswa Sekolah Dasar - Ulya Maysyaroh; Ulfa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The transformation of twenty-first-century education requires assessment systems that extend beyond measuring knowledge acquisition to encompass character development, critical thinking skills, and the application of values in real-life contexts. This study aims to develop a conceptual model of visual media-based learning assessment to strengthen the internalisation of Religious and Character Education values among primary school pupils through the integration of Piaget’s cognitive development theory, Vygotsky’s constructivist theory, and Mayer’s Cognitive Theory of Multimedia Learning. The research employed a qualitative approach using a literature review and conceptual analysis of relevant scholarly sources. Data were analysed through content analysis involving concept identification, theoretical synthesis, thematic categorisation, and conceptual model development. The findings indicate that visual media can enhance assessment practices by making them more contextual, reflective, and authentic, enabling learners to connect abstract concepts with concrete experiences. The integration of the three theoretical perspectives resulted in a five-stage assessment model comprising competency identification, character indicator mapping, contextual visual media selection, reflective assessment, and multidimensional evaluation. The proposed model facilitates a more comprehensive assessment of cognitive, affective, and psychomotor domains while supporting character development among learners.